Preparation method and application of modified porous carbon material for nano silicon CVD (chemical vapor deposition)

By assembled porous two -dimensional sheet materials in porous carbon materials to form a modified porous carbon material, and optimize nano -silicon deposition through spray drying and fluidized bed technology, solving the problem of uneven deposition and poor fluidization status , Achieve high -performance nano -silicon carbon composite negative materials.

CN119351992APending Publication Date: 2025-01-24NINGBO FULI BATTERY MATERIAL TECH CO LTD +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411547182.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When the prior art deposits nanosilicon into porous carbon materials by CVD method, there are problems of uneven deposition and poor fluidization state, resulting in high floating silicon content, poor electrochemical performance and poor batch stability.

Method used

By assembling porosity -free two -dimensional sheet materials and porous carbon materials to form a modified porous carbon material, use spray drying technology to disperse raw materials, optimize the fluidization form in the fluidized bed equipment, and promote the uniform deposition of nano -silicon.

Benefits of technology

The uniform deposition of nano -silicon is realized, the content of floating silicon is reduced, the electrochemical properties and batch stability of the negative electrode materials are improved, and the energy storage characteristics of the lithium ion battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of battery materials, in particular to a preparation method and application of a modified porous carbon material for nano silicon CVD (chemical vapor deposition). According to the invention, the non-porous two-dimensional lamellar material is self-assembled on the porous carbon material, so that the modified porous carbon material for CVD deposition of nano-silicon is obtained, when high-speed carrier gas passes through the surface of the porous carbon material, the two-dimensional lamellar material on the surface of the porous carbon material is stressed intensively, and is not dispersed due to a pore channel structure on the surface of the porous carbon material; therefore, under the same fluidization condition, the modified porous carbon material shows better fluidization characteristics, deposition of nano silicon is more uniform after silane or organic gas is subsequently introduced, the content of floating silicon on the surface is extremely low, silicon enrichment can be reduced while the capacity of the negative electrode material is ensured, and the service life of the negative electrode material is prolonged. Furthermore, the electrochemical performance of the obtained nano silicon-carbon composite negative electrode material is more prominent, and the performance stability of negative electrode materials produced in different batches is also good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of battery materials, and in particular to a preparation method of a modified porous carbon material for CVD deposition of nano-silicon and an application thereof. Background Art

[0002] With the widespread popularity of lithium-ion batteries in electric vehicles, users have put forward higher requirements for the energy density of batteries. Silicon-based negative electrodes have extremely high theoretical specific capacity and are considered to be a powerful additive to further improve the energy storage characteristics of batteries. However, silicon has a serious volume effect during the lithium ion embedding process, which limits its commercial application. Nano-silicon is deposited into the nanopores of porous carbon by CVD. The resulting nano-silicon-carbon negative electrode material can significantly improve the expansion problem, has stable cycle performance, and is increasingly in demand in battery cell applications.

[0003] Compared with horizontal rotary deposition equipment, CVD fluidized bed has the characteristics of uniform deposition, high silane utilization rate and good batch stability, and has received the most attention in mass production equipment. However, as the main solid-phase reaction raw material in the process of fluidized bed deposition of nano-silicon, the fluidization state of porous carbon is not ideal. The fluidization state determines the efficiency of nano-silicon deposition and also determines the uniformity and consistency of nano-silicon deposition into the porous carbon pores. The main reason for the poor fluidization state of porous carbon is that porous carbon originally has a rich pore structure, including through holes, closed holes and semi-open holes. When high-speed carrier gas passes through the surface of porous carbon, due to its rich surface pore structure and dispersed force, the internal bed is prone to channel flow and stagnation, resulting in poor fluidization. The subsequent uneven deposition when silane or organic gas is introduced is prone to produce surface floating silicon, which affects the batch stability of production, and the electrochemical performance of the resulting nano-silicon carbon negative electrode material does not meet expectations.

[0004] Patent CN116588933A discloses a method for preparing nano silicon carbon based on modified activated carbon. In this method, activated carbon is carbonized by passing CO2 at 500-800°C and then nano-deposited. The introduction of CO2 can activate the pores, which is beneficial to the cracking and deposition of silane to a certain extent, but does not significantly improve the fluidization state of porous carbon.

[0005] In patent CN115020689B, a nano-silicon-carbon composite material for secondary lithium batteries is disclosed. This type of material consists of a porous carbon matrix, a coating containing transition metal elements and nano-silicon particles. The coating covers the inside of the porous carbon pores and the surface of the microspheres, preventing the nano-silicon particles from reacting with the porous carbon matrix to form silicon carbide during the deposition process. This method aims to reduce the irreversible capacity loss caused by the formation of SiC by physical isolation, but the coating will reduce the proportion of lithium storage active substances inside the material, and the coating process is complicated, which is easy to block the through holes, and also increases the preparation cost of the material.

[0006] In patent CN116995216A, a silicon-based negative electrode material with a nano-assembly structure is disclosed, which is composed of nitrogen-containing porous silicon carbon nanosheets, low-dimensional nano silicon carbon and coated carbon. It is attempted to provide more points for the deposition of nano silicon through self-assembly of nitrogen-containing porous carbon nanosheets and low-dimensional nano carbon, so that the silicon deposition is uniform, the dispersion is good, and the coated carbon is uniform and dense. The preparation cost of the porous carbon nanosheets described in this method is high, and it is difficult to form a densely packed carbon porous substrate by self-assembly. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is to provide a preparation method and application of a modified porous carbon material for CVD deposition of nano-silicon. The modified porous carbon material obtained by the preparation method provided by the present invention can deposit nano-silicon more evenly during CVD deposition, thereby obtaining a negative electrode material with a low floating silicon content, thereby improving the electrochemical properties of the obtained negative electrode material, and the performance stability of different batches is good.

[0008] The present invention provides a method for preparing a modified porous carbon material for CVD deposition of nano-silicon, comprising the following steps:

[0009] After the raw materials including the porous carbon material and the non-porous two-dimensional sheet material are homogeneously dispersed, the raw materials are spray-dried to obtain a modified porous carbon material for CVD deposition of nano-silicon;

[0010] The non-porous two-dimensional sheet material includes one or more of a two-dimensional carbon material based on graphene sheets, Mxene, invisible carbon microsheets, boron nitride, molybdenum disulfide, tungsten disulfide, sheet metal oxides, black phosphorus or topological insulators.

[0011] Specifically, the non-porous two-dimensional sheet material of the present invention can be self-assembled with a porous carbon material. The non-porous two-dimensional sheet material of the present invention includes one or more of a two-dimensional carbon material based on a graphene sheet, Mxene, an invisible carbon micro-sheet, boron nitride, molybdenum disulfide, tungsten disulfide, a sheet metal oxide, black phosphorus or a topological insulator, wherein the two-dimensional carbon material graphene of the graphene sheet is one or more of graphene, graphene oxide or micro-sheet graphite; the topological insulator is selected from one or more of Sb2Se3, Bi2Se3, Bi2Te3 and Sb2Te3.

[0012] The raw materials of the present invention also include a qiaolian medium material, which can make the modified porous carbon material contain a qiaolian medium to avoid partial shedding of the two-dimensional sheet. In some embodiments of the present invention, the raw materials including the porous carbon material, the non-porous two-dimensional sheet material and the qiaolian medium material are homogenously dispersed and then spray-dried to obtain a modified porous carbon material for CVD deposition of nano-silicon; the non-porous two-dimensional sheet material is one or more of graphene or Mxene. The cross-linking medium of the present invention includes one or more of amorphous carbon or metal oxides; wherein the amorphous carbon as the cross-linking medium can be derived from one or more of ascorbic acid, glucose, fructose, maltose, chitosan, sucrose, carboxymethyl cellulose, gelatin, konjac gum, asphalt, starch, epoxy resin, phenolic resin, polyvinyl alcohol, and polyvinyl pyrrolidone; the metal oxide as the cross-linking medium can specifically be one or more of MnO2, TiO2, Al2O3, ZrO2, SnO2, ZnO, Fe2O3, and Co3O4, and the MnO2 is derived from one or more of potassium permanganate, manganese carbonate, manganese acetate, and manganese nitrate; the TiO2 is derived from titanium alkoxide , titanium tetrachloride, titanium oxysulfate, titanium sulfate; the Al2O3 is derived from one or more of aluminum hydroxide, aluminum nitrate, aluminum chloride, and aluminum sulfate; the ZrO2 is derived from one or more of zirconium hydroxide, zirconium oxychloride, zirconium sulfate, zirconium chloride, and zirconium nitrate; the SnO2 is derived from one or more of tin tetrachloride, tin hydroxide, tin sulfate, tin chloride, and tin nitrate; the ZnO is derived from one or more of zinc hydroxide, zinc sulfate, zinc chloride, and zinc nitrate; the Fe2O3 is derived from one or more of ferric hydroxide, ferric sulfate, ferrous sulfate, ferric chloride, ferric nitrate, and ferrous nitrate; the Co3O4 is derived from one or more of cobalt hydroxide, cobalt sulfate, cobalt acetate, cobalt chloride, and cobalt nitrate.

[0013] After the modified porous carbon material is obtained in the present invention, the non-porous two-dimensional sheet material still exists in the modified porous carbon material, and the non-porous two-dimensional sheet material accounts for 0.5% to 5% of the modified porous carbon material. In the present invention, if the raw material includes a Qiaolian medium material, the mass proportion of the Qiaolian medium formed by the Qiaolian medium material in the modified porous carbon material is 0.1% to 2%. The amount of the non-porous two-dimensional sheet material added in the present invention should not be too much, otherwise it will cause the final modified porous carbon material to be used for the preparation of negative electrode materials, and the reversible capacity of the negative electrode material obtained will be reduced.

[0014] The thickness of the non-porous two-dimensional sheet material of the present invention does not exceed 500 nm. In the present invention, the non-porous two-dimensional sheet material with a thickness exceeding 500 nm, on the one hand, is close to three-dimensional on a microscopic scale, which impairs the effect that it can play as a sheet material; on the other hand, in theory, the grafted sheet of the present invention is to provide a force point for the material itself and optimize the fluidization effect, so there is no need for too high a thickness.

[0015] The D50 of the non-porous two-dimensional sheet material of the present invention does not exceed 60% of the D50 of the porous carbon material. The present invention can avoid the ionic steric effect as much as possible by limiting the D50 of the non-porous two-dimensional sheet material. The porous carbon materials of the present invention are selected from one or more of bio-based porous carbon, petroleum coke-based porous carbon or resin-based porous carbon; the D50 of the porous carbon materials is 3 μm~15 μm.

[0016] The homogeneous dispersion method described in the present invention includes but is not limited to gas phase hydrolysis method, sol-gel method, microemulsion method, hydrothermal synthesis method or gas phase method; the selected homogeneous dispersion method has basically no effect on the specific surface area, pore volume and average pore size of the porous carbon material.

[0017] The temperature of the spray drying of the present invention is 200°C to 500°C, preferably 200°C to 250°C, and more preferably 220°C; the rotation speed of the atomizer used for the spray drying is 20000 r / min to 25000 r / min, and preferably 22000 r / min; the speed of the spray drying is 8 L / h to 12 L / h, and preferably 10 L / h.

[0018] The present invention self-assembles a non-porous two-dimensional sheet material on a porous carbon material. The non-porous two-dimensional sheet material does not affect the subsequent deposition of nano-silicon, can promote or induce nano-silicon to quickly fill the pores, can be stably used in lithium-ion battery materials, does not produce electrochemical side reactions with the electrolyte, is stable in a charged state, and increases the contact area between the obtained modified porous carbon material and the carrier gas during fluidized bed nano-silicon deposition, effectively improves the fluidization morphology of the porous carbon material in the fluidized bed equipment, and promotes the uniform deposition of nano-silicon.

[0019] The present invention also provides a modified porous carbon material obtained by the above preparation method, comprising:

[0020] Porous carbon materials;

[0021] A non-porous two-dimensional sheet material disposed on the porous carbon material;

[0022] Or, include:

[0023] Porous carbon materials;

[0024] A non-porous two-dimensional sheet material disposed on the porous carbon material;

[0025] A cross-linking medium is disposed on the porous carbon material.

[0026] The porous carbon material and the non-porous two-dimensional sheet material described in the present invention are the same as those described above and will not be described in detail; the Qiaolian medium is derived from the Qiaolian medium material, which is the same as those described above and will not be described in detail.

[0027] Among them, the mass proportion of the non-porous two-dimensional sheet material in the modified porous carbon material is 0.5%~5%; if the modified porous carbon material includes a cross-linked medium, the mass proportion of the cross-linked medium in the modified porous carbon material is 0.1%~2%.

[0028] The present invention also provides a negative electrode material, which includes a core material and carbon coated on the core material; the core material includes a modified porous carbon material and nano-silicon deposited on the porous carbon material; the modified porous carbon material is a modified porous carbon material obtained by any of the above-mentioned methods for preparing modified porous carbon materials. The content of nano-silicon in the negative electrode material of the present invention accounts for 40 wt% to 55 wt%, and the carbon coating accounts for 1.5 wt% to 6 wt%.

[0029] The present invention also provides a method for preparing a negative electrode material, comprising: silane deposition and organic carbon coating; specifically, comprising the following steps: sequentially performing CVD deposition on a modified porous carbon material under a silicon source and a carbon source to obtain a negative electrode material; the modified porous carbon material is a modified porous carbon material obtained by any of the above methods for preparing a modified porous carbon material. In certain embodiments of the present invention, a silicon source is introduced into the modified porous carbon material at 450°C to 550°C for CVD deposition, and then a carbon source is introduced into the modified porous carbon material at 560°C to 700°C for CVD deposition to obtain a negative electrode material. The negative electrode material obtained by the present invention is the same as that described above and will not be described in detail.

[0030] The deposition method of the present invention is a CVD deposition method, and the equipment can be a vacuum furnace, a fluidized bed or a horizontal rotary furnace. In some embodiments of the present invention, the modified porous carbon material is placed in a CVD device, and a silicon source is introduced at a flow rate of 2.5 L / min~3.5 L / min at 450℃~550℃ with a CVD carrier gas flow rate of 13 L / min~17 L / min for CVD deposition, and then a carbon source is introduced at a flow rate of 1.3 L / min~2.5 L / min at 560℃~700℃ for CVD deposition to obtain a negative electrode material. The silicon source of the present invention is a gas phase silicon source, specifically including one or more of monosilane, trisilane, dichlorosilane, trichlorosilane or tetrachlorosilane. The carbon source of the present invention is a gas phase carbon source, specifically including one or more of methane, ethylene, acetylene or propane.

[0031] The present invention also provides a negative electrode, comprising a current collector and a negative electrode material disposed on the current collector; the negative electrode material is the above-mentioned negative electrode material and will not be described in detail. In certain embodiments of the present invention, the above-mentioned negative electrode material, SWCNTs, carbon black SP and PAA are mixed and coated on the current collector to obtain the negative electrode. In certain embodiments of the present invention, the mass ratio of the negative electrode material, SWCNTs, carbon black SP and PAA is (80~85): (0.7~1.3): (7~13): (3~7), preferably 84:1:10:5. In certain embodiments of the present invention, the current collector is copper foil. In certain embodiments of the present invention, the coating thickness is 70 μm~90 μm, preferably 80 μm.

[0032] The present invention also provides a battery, comprising a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte; the negative electrode is the negative electrode described above, which will not be described in detail. In certain embodiments of the present invention, the positive electrode is a metal lithium sheet; the separator is a PP / PE separator; and the electrolyte is a LiPF6 / (EC+DEC+DMC) electrolyte.

[0033] The present invention provides a preparation method and application of a modified porous carbon material for CVD deposition of nano silicon. The present invention obtains a modified porous carbon material for CVD deposition of nano silicon by self-assembling a non-porous two-dimensional sheet material on a porous carbon material. When a high-speed carrier gas passes through the surface of the porous carbon material, the force is concentrated at the two-dimensional sheet material on the porous carbon surface, and the force is not dispersed due to the pore structure of the porous carbon surface. Therefore, under the same fluidization conditions, the modified porous carbon material in the present invention exhibits better fluidization characteristics. In this way, the channel flow and throttling of the internal bed can be avoided. After the subsequent introduction of silane or organic gas, the deposition of nano silicon is more uniform, and the surface floating silicon content is extremely low. The extremely low floating silicon content can reduce the enrichment of silicon while ensuring the capacity of the negative electrode material, thereby reducing the volume expansion during the charge and discharge process, and the cycle and high and low temperature storage performance are better, and the electrochemical performance of the obtained nano silicon carbon composite negative electrode material will be more prominent, and the performance stability of the negative electrode materials produced in different batches is also good. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a SEM image of the porous carbon substrate coated with graphene microsheets obtained in Example 3 of the present invention;

[0035] Figure 2 This is a SEM image of the porous carbon substrate mixed with graphene sheets obtained in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0036] The present invention discloses a preparation method of a modified porous carbon material for CVD deposition of nano-silicon and its application. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0037] The present invention will be further described below in conjunction with embodiments:

[0038] Example 1

[0039] 1 kg of resin-based porous carbon (D50 is 7.5 μm) was added to 15 L of aqueous solution, and 2% PVP was added. After complete dispersion, 10 g / L of Mxene dispersion (number of layers ≤ 5 layers, D50 is 3 microns) was added. After homogeneous dispersion, spray drying was performed at a drying temperature of 220°C, an atomizer speed of 22000 r / min, and a drying speed of 10 L / h. A porous carbon substrate grafted with Mxene was obtained. The specific surface area, pore volume, and average pore size test results of porous carbon before and after modification are shown in Table 1.

[0040] 1 kg of the obtained porous carbon was added to the fluidized bed CVD equipment. The fluidized bed carrier gas flow rate was adjusted to 15 L / min, and the motor stirring rate was 100 rpm / min. After the temperature was raised to 520°C, monosilane was introduced with a silane flow rate of 3 L / min and ventilation for 268 min; the temperature in the furnace was raised to 640°C, acetylene was introduced for amorphous carbon coating, the flow rate was set to 1.5 L / min, and ventilation was performed for 150 min. After cooling, the final nano-silicon-carbon composite negative electrode material was obtained. Its related silicon deposition performance is shown in Table 2.

[0041] In addition, the above negative electrode materials were assembled into CR2032 button cells. The preparation method is as follows: the nano silicon carbon negative electrode material is homogenized according to the following ratio: active material (84%), SWCNTs (1%), carbon black SP (10%), PAA (5%). The obtained slurry is coated on a copper foil of 8 μm, and the coating thickness is 80 μm. After the negative electrode slurry is applied by scraping, it is dried, rolled and punched. The prepared negative electrode sheet is used as the positive electrode, the metal lithium sheet is used as the negative electrode, PP / PE is used as the separator, and LiPF6 / EC+DEC+DMC (the volume ratio of EC, DEC and DMC is 1:1:1) is used as the electrolyte, and assembled in an argon-filled glove box. The upper limit of the charging voltage is 2V, the lower limit of the discharge is 0.005V, the first cycle charge and discharge rate is 0.1C, and the cycle rate is 0.2C. Its electrochemical properties are shown in Table 2.

[0042] Example 2

[0043] 1 kg of resin-based porous carbon (D50 is 7.5 μm) was added to 15 L of aqueous solution, and 2% PVP was added. After complete dispersion, 1.5 L of 10 g / L Mxene dispersion (number of layers ≤ 5, D50 is 3 microns) was added. After homogeneous dispersion, spray drying was performed at a drying temperature of 220°C, an atomizer speed of 22000 r / min, and a drying speed of 10 L / h. A porous carbon substrate grafted with Mxene was obtained. The specific surface area, pore volume, and average pore size test results of porous carbon before and after modification are shown in Table 1.

[0044] 1 kg of the obtained porous carbon was added to the fluidized bed CVD equipment. The fluidized bed carrier gas flow rate was adjusted to 15 L / min, and the motor stirring rate was 100 rpm / min. After the temperature was raised to 520°C, monosilane was introduced with a silane flow rate of 3 L / min and ventilation for 280 min; the temperature in the furnace was raised to 640°C, and acetylene was introduced for amorphous carbon coating, with a flow rate of 1.5 L / min and ventilation for 150 min. After cooling, the final nano-silicon-carbon composite negative electrode material was obtained. The relevant properties are shown in Table 2.

[0045] In addition, the above negative electrode materials were assembled into CR2032 button cells. The preparation method was the same as that of Example 1. The electrochemical properties thereof are shown in Table 2.

[0046] Example 3

[0047] 3 kg of resin-based porous carbon (D50 is 5 μm) was added to the VC mixer and stirred and preheated to 200°C, and a nitrogen protective atmosphere was introduced. 1.5 L of a 2% solid content graphene microsheet dispersion (number of layers ≤ 5, D50 is 3 microns, containing 0.5% CMC) was slowly sprayed into the reactor at a stirring rate of 150 rpm / min. A porous carbon substrate coated with graphene microsheets was obtained. Figure 1 As shown, Figure 1 This is a SEM image of the porous carbon substrate coated with graphene microsheets obtained in Example 3 of the present invention. The test results of the specific surface area, pore volume and average pore diameter of the porous carbon before and after modification are shown in Table 1.

[0048] 1 kg of the obtained porous carbon was added to the fluidized bed CVD equipment. The fluidized bed carrier gas flow rate was adjusted to 15 L / min, and the motor stirring rate was 100 rpm / min. After the temperature was raised to 520°C, monosilane was introduced with a silane flow rate of 3 L / min and ventilation for 280 min; the temperature in the furnace was raised to 640°C, and acetylene was introduced for amorphous carbon coating, with a flow rate of 1.5 L / min and ventilation for 150 min. After cooling, the final nano-silicon-carbon composite negative electrode material was obtained. The relevant properties are shown in Table 2.

[0049] In addition, the above negative electrode materials were assembled into CR2032 button cells. The preparation method was the same as that of Example 1. The electrochemical properties thereof are shown in Table 2.

[0050] Example 4

[0051] 500 g of petroleum coke-based porous carbon (D50 is 9 μm) was dispersed in 6.5 L of deionized water, and 200 mL of 1M potassium permanganate solution and 0.5 L of graphene dispersion with a solid content of 0.5% were added. After hydrothermal reaction at 150 ° C for 12 h, it was filtered out and dried. A porous carbon substrate grafted with graphene sheets was obtained, in which the graphene sheets and the porous carbon substrate were connected by MnO2 microsheets. The specific surface area, pore volume and average pore size test results of porous carbon before and after modification are shown in Table 1.

[0052] 1 kg of the porous carbon was added to the fluidized bed CVD equipment. The carrier gas flow rate of the fluidized bed was adjusted to 15 L / min, and the motor stirring rate was 100 rpm / min. After the temperature was raised to 520°C, monosilane was introduced with a silane flow rate of 3 L / min and ventilation for 268 min; the temperature in the furnace was raised to 640°C, and methane was introduced for amorphous carbon coating, with a flow rate of 2 L / min and ventilation for 120 min. After cooling, the final nano-silicon-carbon composite negative electrode material was obtained. The relevant properties are shown in Table 2.

[0053] In addition, the above negative electrode materials were assembled into CR2032 button cells. The preparation method was the same as that of Example 1. The electrochemical properties thereof are shown in Table 2.

[0054] Example 5

[0055] 500 g of bio-based porous carbon (D50 is 15 μm) was dispersed in 5 L of deionized water solution, and 500 mL of graphene oxide solution with a solid content of 3% (D50 is 6 μm) was added. After homogeneous dispersion, spray drying was performed at a drying temperature of 220°C, an atomizer speed of 22000 r / min, and a drying speed of 10 L / h. A porous carbon substrate grafted with graphene oxide sheets was obtained. The specific surface area, pore volume and average pore size test results of porous carbon before and after modification are shown in Table 1.

[0056] 1 kg of the porous carbon was added to the fluidized bed CVD equipment. The carrier gas flow rate of the fluidized bed was adjusted to 15 L / min, and the motor stirring rate was 100 rpm / min. After the temperature was raised to 520°C, trichlorosilane was introduced, the silane flow rate was 3.3 L / min, and the ventilation was carried out for 250 min; the temperature in the furnace was raised to 580°C, and amorphous carbon was coated by ethylene, the flow rate was set to 2.3 L / min, and the ventilation was carried out for 120 min. After cooling, the final nano-silicon-carbon composite negative electrode material was obtained. The relevant properties are shown in Table 2.

[0057] In addition, the above negative electrode materials were assembled into CR2032 button cells. The preparation method was the same as that of Example 1. The electrochemical properties thereof are shown in Table 2.

[0058] Comparative Example 1

[0059] This comparative example 1 is compared with Example 1, and the porous carbon is not cross-linked, as follows: 1 kg of resin-based porous carbon (D50 is 8 μm) is added to the fluidized bed CVD equipment. The carrier gas of the fluidized bed CVD equipment is increased from 15 L / min to 20 L / min, and the stirring rate of the bottom motor is increased from 100 rpm / min to 150 rpm / min; after the rate temperature is increased to 520°C, monosilane is introduced, the silane flow rate is 3 L / min, and the ventilation is 268 min; the temperature in the furnace is increased to 640°C, acetylene is introduced for amorphous carbon coating, the flow rate is set to 1.5 L / min, and the ventilation is 150 min. After cooling, the final nano-silicon-carbon composite negative electrode material is obtained. The amount of nano-silicon deposition and the floating silicon content are shown in Table 2.

[0060] In addition, the above negative electrode materials were assembled into CR2032 button cells. The preparation method was the same as that of Example 1. The electrochemical properties thereof are shown in Table 2.

[0061] It can be seen from this comparative example 1 that even if the fluidization dynamics of the fluidized bed are changed, the effect cannot be achieved without two-dimensional sheet modification.

[0062] Comparative Example 2

[0063] 1 kg of resin-based porous carbon (D50 is 8 μm) was added to 15 L of aqueous solution. After complete dispersion, 3 L of graphene dispersion with a solid content of 3% (containing 0.3% CMC, the number of graphene layers ≤5 layers, and D50 of 5 μm) was added. After homogeneous dispersion, spray drying was performed at a drying temperature of 220°C, an atomizer speed of 22000 r / min, and a drying speed of 10 L / h. A porous carbon substrate with excessive graphene sheets grafted on it was obtained. The specific surface area, pore volume, and average pore size test results of the porous carbon before and after modification are shown in Table 1.

[0064] 1 kg of the obtained porous carbon was added to the fluidized bed CVD equipment. The carrier gas flow rate of the fluidized bed was adjusted to 15 L / min, and the motor stirring rate was 100 rpm / min. After the temperature was raised to 520°C, monosilane was introduced with a silane flow rate of 3 L / min and ventilation for 268 min; the temperature in the furnace was raised to 640°C, and acetylene was introduced for amorphous carbon coating, with a flow rate of 1.5 L / min and ventilation for 150 min. After cooling, the final nano-silicon-carbon composite negative electrode material was obtained. The amount of nano-silicon deposition and the floating silicon content are shown in Table 2.

[0065] In addition, the above negative electrode materials were assembled into CR2032 button cells. The preparation method was the same as that of Example 1. The electrochemical properties thereof are shown in Table 2.

[0066] Comparative Example 3

[0067] 3 kg of resin-based porous carbon (D50 is 5 μm) was added to the VC mixer and stirred and preheated to 200 °C, and a nitrogen protective atmosphere was introduced. 600 mL of a 5% solid content graphite microplatelet dispersion (irregular particles, D50 is 2 μm, containing 0.5% CMC) was slowly sprayed into the reactor at a stirring rate of 150 rpm / min. A porous carbon substrate with graphite microplatelets was obtained. The specific surface area, pore volume and average pore size test results of porous carbon before and after modification are shown in Table 1.

[0068] 1 kg of the obtained porous carbon was added to the fluidized bed CVD equipment. The carrier gas flow rate of the fluidized bed was adjusted to 15 L / min, and the motor stirring rate was 100 rpm / min. After the temperature was raised to 520°C, monosilane was introduced with a silane flow rate of 3 L / min and ventilation for 268 min; the temperature in the furnace was raised to 620°C, and acetylene was introduced for amorphous carbon coating, with a flow rate of 1.5 L / min and ventilation for 150 min. After cooling, the final nano-silicon-carbon composite negative electrode material was obtained. The relevant properties are shown in Table 2.

[0069] In addition, the above negative electrode materials were assembled into CR2032 button cells. The preparation method was the same as that of Example 1. The electrochemical properties thereof are shown in Table 2.

[0070] Comparative Example 4

[0071] 3 kg of resin-based porous carbon (D50 is 5 μm) and 150 g of graphene powder (D50 is 3 μm) were added to a planetary ball mill. After adding ball milling beads at a ball-to-material ratio of 1:1, the mixture was ball milled at 350 rpm / min for 30 min to obtain a porous carbon substrate mixed with graphene sheets. The SEM image is shown in Figure 2. Figure 2 As shown, Figure 2 This is a SEM image of the porous carbon substrate mixed with graphene sheets obtained in Comparative Example 4 of the present invention. The test results of its specific surface area, pore volume and average pore diameter are shown in Table 1.

[0072] 1 kg of the porous carbon substrate was added to the fluidized bed CVD equipment. The carrier gas flow rate of the fluidized bed was adjusted to 15 L / min, and the motor stirring rate was 100 rpm / min. After the temperature was raised to 520°C, monosilane was introduced with a silane flow rate of 3 L / min for 268 min; the temperature in the furnace was raised to 620°C, acetylene was introduced for amorphous carbon coating, the flow rate was set to 1.5 L / min, and the ventilation was carried out for 150 min. After cooling, the final nano-silicon-carbon composite negative electrode material was obtained. The relevant properties are shown in Table 2.

[0073] In addition, the above negative electrode materials were assembled into CR2032 button cells. The preparation method was the same as that of Example 1. The electrochemical properties thereof are shown in Table 2.

[0074] Table 1

[0075]

[0076] Table 2

[0077]

[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a modified porous carbon material for CVD deposition of nano-silicon, characterized in that: The following steps are involved: After the raw materials including the porous carbon material and the non-porous two-dimensional sheet material are homogeneously dispersed, the raw materials are spray-dried to obtain a modified porous carbon material for CVD deposition of nano-silicon; The non-porous two-dimensional sheet material includes one or more of a two-dimensional carbon material based on graphene sheets, Mxene, invisible carbon microsheets, boron nitride, molybdenum disulfide, tungsten disulfide, sheet metal oxides, black phosphorus or topological insulators.

2. The method for preparing a modified porous carbon material according to claim 1, characterized in that: The raw material also includes a qiaolian medium material, so that the modified porous carbon material contains a qiaolian medium; the qiaolian medium includes one or more of amorphous carbon or metal oxides; The non-porous two-dimensional sheet material is one or more of graphene or Mxene.

3. The method for preparing a modified porous carbon material according to claim 2, characterized in that: The mass proportion of the Qiaolian medium in the modified porous carbon material is 0.1%~2%.

4. The method for preparing a modified porous carbon material according to any one of claims 1 to 3, characterized in that: The mass proportion of the non-porous two-dimensional sheet material to the modified porous carbon material is 0.5% to 5%.

5. The method for preparing a modified porous carbon material according to any one of claims 1 to 3, characterized in that: The D50 of the porous carbon material is 3 μm to 15 μm; The D50 of the nonporous two-dimensional sheet material does not exceed 60% of the D50 of the porous carbon material.

6. A negative electrode material, characterized in that It includes a core material and carbon coated on the core material; The core material comprises a modified porous carbon material and nano-silicon deposited on the modified porous carbon material; The modified porous carbon material is a modified porous carbon material obtained by the preparation method of the modified porous carbon material according to any one of claims 1 to 5.

7. The negative electrode material according to claim 6, characterized in that The content of nano-silicon in the negative electrode material accounts for 40 wt%~55 wt%, and the carbon coating accounts for 1.5 wt%~6 wt%.

8. A method for preparing a negative electrode material, characterized in that: The following steps are involved: A silicon source is introduced into the modified porous carbon material at 450° C. to 550° C. for CVD deposition, and then a carbon source is introduced into the modified porous carbon material at 560° C. to 700° C. for CVD deposition to obtain a negative electrode material; The modified porous carbon material is a modified porous carbon material obtained by the preparation method of the modified porous carbon material according to any one of claims 1 to 5.

9. A negative electrode, characterized in that comprising a current collector and a negative electrode material disposed on the current collector; The negative electrode material is the negative electrode material according to claim 6 or 7 or the negative electrode material obtained by the preparation method of the negative electrode material according to claim 8.

10. A battery, characterized in that: It includes a positive electrode, a negative electrode, a separator and an electrolyte disposed between the positive electrode and the negative electrode; The negative electrode is the negative electrode according to claim 9.

Citation Information

Cited By

  • Porous silicon-carbon composite material, negative pole piece, secondary battery and preparation method

    CN121394353A

  • Silicon-carbon composite negative electrode material and preparation method and application thereof

    CN121460562A

  • A silicon-carbon composite anode material, its preparation method and application

    CN121460562B